'They have just given up on me' How pupils labelled with social, emotional and behavioural difficulties (SEBD) experience the process of exclusion from school. Issue 1 (26th January 2021) - Caslin, Marie
Abstract : For decades, the school exclusion rates have been a cause for concern within the English education system. We have witnessed a steady increase in the numbers of pupils being excluded since 2012. Evidence suggests that some children are more likely to be excluded from school, a significant number will have had the social, emotional and behavioural difficulties label attached to them. This article will draw on the work of Parsons and Howlett (Permanent exclusions from school: A case where society is failing its children. Support for Learning, 11, 3, 109–112, 1996) to see how much, if any, progress has been made since the publication of their work which raised concerns regarding the exclusion processes employed in England. Drawing on the perspectives of pupils, parents and teachers, 13 in‐depth case studies were developed, with emphasis placed on employing innovative and creative methods to hear the voices of young people. The findings revealed that young people, their parents and teachers feel the current education system continues to fail this group of young people.